The Effect of the Changing Size and Composition of Government Purchases on Potential Output: A Comment - Reid, Bradford G. (The Review of Economics and Statistics, 1982)
Bradford G. Reid, The Effect of the Changing Size and Composition of Government Purchases on Potential Output: A Comment, The Review of Economics and Statistics, Vol. 64, No. 3 (Aug., 1982), pp. 525-527